The Role of Community Nurses in Improving Public Health: Strategies and Implementation of Educational Programs - Paulus Subiyanto; Masruroh; Catur Budi Susilo; Destiana (PT. Anagata Sembagi Education, 2024)
Community nurses play an important role in improving community health through the implementation of educational strategies and programmes tailored to local needs. This study aims to explore the role of community nurses in designing, implementing and evaluating health education programmes to improve the quality of community health. The methodology used included an extensive literature review and case study analysis of several communities that have adopted such programmes. The results showed that community nurses contribute significantly to improving health awareness, knowledge and behaviours, resulting in improved quality of life and reduced incidence of preventable diseases. Effective education programmes are designed using interactive learning methods, such as workshops, group discussions and individual counselling, tailored to the characteristics of the local community. The success of the programme relies heavily on a collaborative approach between nurses, communities and local health stakeholders. Ongoing support through professional training and increased community engagement are key factors for long-term success. This study concludes that the role of community nurses extends beyond basic medical care to include functioning as change agents in sustainable health promotion. Recommendations include strengthening the capacity of community nurses through ongoing training and developing policies that support the integration of this role in a holistic public health system.